2008
DOI: 10.2337/dc07-1286
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Time Spent Sedentary Is Associated With Insulin Resistance Independent of Overall and Central Body Fat in 9- to 10-Year-Old Portuguese Children

Abstract: RESEARCH DESIGN AND METHODS:School-based, cross-sectional study in 259 girls (9.8 ± 0.3 years; 18.0 ± 3.3 kg/m²; 27.8 ± 9.3 % body fat) and 274 boys (9.8 ± 0.3 years;18.24± 3.5 kg/m²; 22.0 ± 9.2 % body fat) randomly selected. Trunk fat mass (FM) and central FM were measured with DXA. Free-living physical activity (PA) was measured with accelerometry for 4 days. We created a standardised continuously distributed clustered metabolic risk variable using the following subcomponents:; blood pressure, fasting glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
3
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(173 citation statements)
references
References 54 publications
11
146
3
13
Order By: Relevance
“…As concerns the association between objectively measured sedentary time and IR, our results are in disagreement with those reported for 9 to 10-yr-old Portuguese children [13] and adults [20], while are in the same line with those detected in adults with a family history of type 2 diabetes [21]. Differences between studies are likely The positive association observed between TV viewing time and IR risk could be explained by a number of mechanisms.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…As concerns the association between objectively measured sedentary time and IR, our results are in disagreement with those reported for 9 to 10-yr-old Portuguese children [13] and adults [20], while are in the same line with those detected in adults with a family history of type 2 diabetes [21]. Differences between studies are likely The positive association observed between TV viewing time and IR risk could be explained by a number of mechanisms.…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, limited data are available regarding the independent associations between different subcomponents of PA (i.e. time spent sedentary, at light-intensity activity and at moderateand vigorous intensity physical activity (MVPA) and self-reported TV viewing) and IR, especially among children/adolescents [13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…1 study found a favourable association between sporadic MVPA and systolic BP (Holman et al 2011) Poitras et al Leary et al 2008;Colley et al 2012;Hearst et al 2012;Mendoza et al 2012;Carson et al 2013 Mendoza et al 2012;Carson et al 2013;Chaput et al 2013;Hjorth et al 2014a;Stabelini Neto et al 2014) MPA: null association (1/1 studies; Stabelini Neto et al 2014) LPA: null associations (2/2 studies; Carson et al 2013;Stabelini Neto et al 2014 Andersen et al 2006;Rizzo et al 2008;Sardinha et al 2008;Owen et al 2010;Hjorth et al 2014a), or null (1/6 studies; Jimenez-Pavon et al …”
Section: Mvpamentioning
confidence: 99%
“…n Includes 47 cross-sectional studies (Brage et al 2004a(Brage et al , 2004bGutin et al 2005b;Wennlof et al 2005;Andersen et al 2006;Ekelund et al 2006Ekelund et al , 2009Hurtig-Wennlof et al 2007;Quiros-Tejeira et al 2007;Rizzo et al 2007Rizzo et al , 2008Butte et al 2007b;Ruiz et al 2007;Leary et al 2008;Mark and Janssen 2008;Sardinha et al 2008;Sakuragi et al 2009;Schofield et al 2009;LeBlanc and Janssen 2010;Nguyen et al 2010;Owen et al 2010;Carson and Janssen 2011;Holman et al 2011;Moreira et al 2011;Colley et al 2012;Hay et al 2012;Hearst et al 2012;Henderson et al 2012;Jimenez-Pavon et al 2012, 2013b, 2013cMartinez-Gomez et al 2012;Mota et al 2012;Mendoza et al 2012;Barreira et al 2013;Carson et al 2013;Chaput et al 2013;Janssen et al 2013;Lamotte et al 2013;Knowles et al 2013;Loprinzi et al 2013;Rey-Lopez et al 2013;…”
Section: Mpamentioning
confidence: 99%
See 1 more Smart Citation